Persepsi Masyarakat Terhadap Pemakai Pakaian Gamis (Studi Deskriptif Tentang Persepsi Masyarakat Lingkungan XV dan VIII Kelurahan Mabar Kecamatan Medan Deli Terhadap Pengguna Pakaian Gamis) - Suheri Suheri (UMSU, 2018)
This study aims to determine the perceptions of Muslim men who wear a robe in the neighborhood of XV and XVIII in Mabar Village, Medan Deli District. Those among the prayer worshipers at a Subulussalam Mosque are ± 40 to 50 in each prayer congregation using the robe clothing. This research method uses a qualitative approach and relies on in-depth observation and interviews with informants who are not users of robe clothing. The results of this study indicate that robe wearers always appear confident and feel comfortable in worship. The knowledge and opinions of informants on robe wearers are as forms and forms of knowledge that can reflect social values in order to increase one's devotion and faith.